2021
DOI: 10.3389/fevo.2021.739817
|View full text |Cite
|
Sign up to set email alerts
|

Landscape-Scale Effects of Fire, Cats, and Feral Livestock on Threatened Savanna Mammals: Unburnt Habitat Matters More Than Pyrodiversity

Abstract: Northern Australia has undergone significant declines among threatened small and medium-sized mammals in recent decades. Conceptual models postulate that predation by feral cats is the primary driver, with changed disturbance regimes from fire and feral livestock in recent decades reducing habitat cover and exacerbating declines. However, there is little guidance on what scale habitat and disturbance attributes are most important for threatened mammals, and what elements and scale of fire mosaics actually supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…These positive responses could be explained by either increased cover mediated by feral cat predation or increased food resources, as allowed by the investigators (Legge et al, 2011). A large-sample observational study (n = 94) found that total small-mammal abundance and diversity increased, and mortality due to feral cats decreased, as three types of cover-rock, shrub, and perennial grass-increased, and as livestock grazing was reduced (Radford et al, 2021). A 13-year natural experiment with varying levels of livestock grazing and fire extent and intensity concluded that fire and domestic LMH each suppressed small mammals (murids and small dasyurid marsupials) and had a negative synergistic-but not additive-effect on overall small-mammal abundance and richness (but opposite effects on P. delicatulus compared to the four other commonly caught species; Legge et al, 2019).…”
Section: Northern Australiamentioning
confidence: 98%
See 2 more Smart Citations
“…These positive responses could be explained by either increased cover mediated by feral cat predation or increased food resources, as allowed by the investigators (Legge et al, 2011). A large-sample observational study (n = 94) found that total small-mammal abundance and diversity increased, and mortality due to feral cats decreased, as three types of cover-rock, shrub, and perennial grass-increased, and as livestock grazing was reduced (Radford et al, 2021). A 13-year natural experiment with varying levels of livestock grazing and fire extent and intensity concluded that fire and domestic LMH each suppressed small mammals (murids and small dasyurid marsupials) and had a negative synergistic-but not additive-effect on overall small-mammal abundance and richness (but opposite effects on P. delicatulus compared to the four other commonly caught species; Legge et al, 2019).…”
Section: Northern Australiamentioning
confidence: 98%
“…Of 17 studies of fire effects conducted in Northern Australia, 12 of which were experimental, six concluded that loss of cover explained significant small-mammal responses (Kutt and Woinarski, 2007;Legge et al, 2008;Kutt and Gordon, 2012;Leahy et al, 2015;Davies et al, 2017;Radford et al, 2021), five concluded that both cover and food resources were partly important as limiting factors (Lawes et al, 2015;McDonald et al, 2016;Ondei et al, 2020;Radford et al, 2020;Penton et al, 2021), and six studies were inconclusive (Pardon et al, 2003;Woinarski et al, 2004;Griffiths and Brook, 2014;Abom et al, 2016;Davies et al, 2018;Legge et al, 2019; Supplementary Table S1, Figure 2). One study found 90% direct mortality of small mammals from intense fires, with the individuals surviving being in unburned refuges (Legge et al, 2008).…”
Section: Northern Australiamentioning
confidence: 99%
See 1 more Smart Citation
“…However, the loss of long-unburnt habitat patches, with respect to both their frequency and overall representation within landscapes, points to the need for active stakeholder collaboration to design appropriate management plans for landscapes that are managed for multiple, sometimes competing, objectives. Recent studies have begun to quantify age-class distributions of vegetation that would benefit species of conservation concern (Giljohann et al 2018), highlighting the need for a greater extent of long-unburnt vegetation (Davies et al 2018;Radford et al 2021), and there may be opportunities to integrate other values and objectives into these tools.…”
Section: Challenges and Opportunities For Contemporary Landscape Mana...mentioning
confidence: 99%
“…Multiple authors have recommended that a priority conservation action was intensive fire management aimed at increasing the extent of longer-unburnt habitat and in delivering fine-scale patch burning [22,23,145]. A mosaic of fire patches of different ages also has been considered to be the best option for a range of birds, mammals, amphibians, and reptiles found in the savanna landscapes [146], but the mosaic hypothesis is not sufficiently nuanced for management to be effective [136].…”
Section: Unsupported Assumptions Related To Fire Managementmentioning
confidence: 99%